Effects of neighbourhood religious diversity and religious and national identity on neighbourhood trust. (August 2022) - Bennett, Matthew R.; Parameshwaran, Meenakshi; Schmid, Katharina; Ramos, Miguel; Hewstone, Miles
This paper examines the relationship between religious diversity, religious and national identity, and neighbourhood trust. Using data from 6, 089 individuals in England matched to census-based statistical estimates for 300 local areas, we find that religious diversity is negatively associated with neighbourhood trust. Further analyses tested indirect relationships between religious diversity and neighbourhood trust to examine whether higher levels of religious diversity are associated with a stronger sense of religious identity, and whether a stronger sense of religious identity is associated with lower levels of neighbourhood trust. We simultaneously tested whether higher levels of religious diversity are associated with a weaker sense of national identity, and whether a weaker sense of national identity is associated with lower neighbourhood trust. Multigroup analyses were conducted to assess patterns across religious groups. Results indicate that, for Christians, religious diversity is associated with a stronger subordinate religious identification, which is in turn associated with lower neighbourhood trust. There were no associations between religious diversity, national identification, and neighbourhood trust. For the other religious groups, no significant associations were found between our variables of interest. We discuss the relevance and implication of increasing religious diversity in societies for the multiple groups involved.